Sprachbildung im naturwissenschaftlichen Sachunterricht Eine Interventionsstudie zur Wirksamkeit fachintegrierter Sprachbildung nach dem Scaffolding-Ansatz und mit Focus-on-Form-Strategien - Siegmund, Benjamin (Sprachlich-Literarisches Lernen und Deutschdidaktik: Bände (SLLD-B), 2022)
Competence in the instructional language seems to be crucial to a successful educational biography. While most children do not lack oral competencies in German, many struggle with the (conceptually) written academic language register ('Bildungssprache') that is the most important medium of learning and performance assessment in school (Feilke, 2012; Gogolin et al., 2013; Morek & Heller, 2012; Heppt & Stanat, 2020; Volodina et al., 2020; Volodina & Weinert, 2020). The mastery of this register is im-portant for learning in all subjects. Even very early science teaching in primary school depends on language competencies. Thus, it is necessary to integrate language and science teaching (vgl. z. B. Rank & Wildemann, 2015). Its focus on interesting facts, observations and experiments qualifies science teaching to play an important role in language learning, because "learning about language is most meaningful when it occurs in the context of actual language use" (Gibbons, 2002, S. 12). Ideas and concepts for the integration of language and science teaching exist (e. g. Gibbons, 2002). However, studies investigating their efficacy are missing. This work tries to contribute in closing this research gap. First, it presents a teaching unit for science teaching in fourth grade that integrates language teaching. Its scientific topic is the process of dissolving substances in water. Based on science teaching methods, the teaching unit integrates language and science teaching by merging Gibbons' scaffolding concept (Gibbons, 2002), focus-on-form techniques from second language learning approaches (e. g. Ellis, 2016) and conceptual change ideas (e.g. Möller, 2015). Second, I conducted a quasi-experimental intervention study with pretest-posttest design, control group and randomised assignment at class level in order to investigate the efficacy of this teaching unit. N = 107 fourth grade students participated in this study, coming from six classrooms within three schools located in Baden-Württemberg, Germany. In this intervention study I taught the unit myself in order to control its implementation and to enhance the comparability of the instruction in the three intervention classrooms. The results of this study show that the intervention had effects on the students regarding their educational language. In the teaching unit, they learnt among other things that conditionals are an appropriate structure to formulate if-clauses in a generalising matter within scientific descriptions of experiments. They also learnt to build and use the German Verb-first-conditional, a conceptually written, academic linguistic structure that is considered to cause difficulties in reading comprehension. They further learnt to (re-)phrase descriptions of experiments in an impersonal, academic way, using the German indefinite pronoun man or passive voice. A test on the scientific topic that was only conducted in the posttest indicates learning achievements in scientific knowledge concerning the process of dissolving substances in water. Thus, the study shows that it is possible to efficaciously integrate language and science teaching in primary schools based on the ideas of scaffolding and focus-on-form techniques.